FAKTOR-FAKTOR YANG MEMPENGARUHIVOLUNTARY AUDITOR SWITCHING (Studi Empiris pada Perusahaan Non Financing yang Terdaftar di Bursa Efek Indonesia tahun 2011-2015) - Ella Soraya; Musfiari Haridhi (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2017)
This study aims to examine empirically the factors that effect the auditor switching voluntarily. Variabels which use in this research is audit delay, change in management and the rate of growth of the cilent company. Voluntary auditor switching is the switchs of KAP before the time given is end. Auditor switching is a displacement behavior by a company auditor as a result of auditor rotation mandatory.Collecting data used a puposive sampling of company listed on Indonesia Stock Exchange in 2011 until 2015. A total of 19 non financing firm are used for sample this study.Using logistic regression analysis this research attempts to examine empirically the influence of audit delay, change in management and company growth of voluntary auditor switching. Results of this research show that audit delay, change in management and company growth  have a significant effect on voluntary auditor switching. Keywords: Voluntary Auditor Switching, Audit Delay, Change in Management, Company Growth.